Lanthanoid β-triketonates: a new class of highly efficient NIR emitters for bright NIR-OLEDs - Reid, Brodie; Stagni, S.; Malicka, J.; Cocchi, M.; Hanan, G.; Ogden, Mark; Massi, Massimiliano (The Royal Society of Chemistry, 2014)
The reaction of hydrated YbCl3 with potassium tribenzoylmethanide yields a new bimetallic tetranuclear Yb3+/K+ assembly. This species not only possesses the longest excited state lifetime and quantum yield reported for the Yb3+ diketonate family but is also suitable to be incorporated in NIR-OLEDs, whose performance outclasses any other reported lanthanoid-based device with NIR emission.